Crystal structures, antioxidant, electrochemical and in-situ spectroelectrochemical properties of new bisthiocarbohydrazones and their Ni(II) complexes - Kaya, Yeliz; Ercag, Ayse; Uguz, Ozlem; Zorlu, Yunus; Koca, Atif (Elsevier Science Sa, 2023)
Four new isatin bisthiocarbohydrazone ligands (H2L1, H2L2, H2L3, H2L4) were synthesized by the condensation of salicylaldehyde, 5-bromosalicylaldehyde, 5-chlorosalicylaldehyde and 5-nitrosalicylaldehyde with isatin monothiocarbohydrazone, respectively. The mixed ligand Ni(II) complexes {[NiL1(P)], [NiL2(P)], [NiL3(P)] and [NiL4(P)]} containing triphenylphosphine (P: triphenylphosphine, PPh3) of these bisthiocarbohydrazone ligands were synthesized. The synthesized compounds were characterized by elemental analysis, FT-IR, 1H NMR, UV-Vis spectroscopy techniques and conductivity measurements. In the complexes, the bisthiocarbohydrazone ligands coordinate to nickel through ONS mode. The complexes are diamagnetic and exhibit square planar geometry. The crystal structures of two ligands, H2L1 and H2L3, and two complexes, [NiL1(P)] and [Ni3(L3)2(P)2], whose single crystals were obtained, were determined by single crystal X-ray diffraction technique. The crystal structure of [NiL1(P)] complex is monomeric and compatible with the structure of the solid complex. A new trinuclear Ni (II) complex, [Ni3(L3)2(P)2], was obtained by the crystallization of monomeric solid [NiL3(P)] complex in a different solvent mixture. Redox properties of bisthiocarbohydrazone ligands (H2L1-H2L4) bearing S1 or S2 substituents and their nickel(II) complexes {[NiL1(P)]-[NiL4(P)]} were investigated with cyclic voltammetry and in situ spectroelectrochemistry. Voltammetric analyses indicated that all ligands exhibited four quasi-reversible reduction and one irreversible oxidation process. Complexation of the ligands with Ni(II) cation decreased the number of the reduction processes and caused these processes to have more negative potentials. Significant spectral changes were also observed in the in situ spectroelectrochemical analysis due to electron transfer re-actions. In addition, electrochemical responses of monosubstituted salicylaldehyde derivative isatin bisthio-carbohydrazone ligands and their nickel(II) complexes were compared with their disubstituted derivatives.
Keywords: Electrochemistry; Bisthiocarbohydrazone; Nickel(II); Crystal structure; Antioxidant